Business Incubator Centers and Their Role in Empowering Micro, Small, and Medium Enterprises in Sidoarjo - Setyawanto, Agus; Hariyadi, Bachtiar; Tontowi; Koroma, Christiana (LPPM Universitas Yudharta Pasuruan, 2023)
Kebonagung Village, a Sukodono District area, is home to a growing number of Micro, Small, and Medium Enterprises (MSMEs) but lacks effective product marketing management. The lack of a Business Incubator Center (BIC) hinders MSMEs from developing their marketing strategies. This study aims to map MSMEs' existing potential and development needs in Kebonagung Village through various BIC networks. The research methodology combines Participatory Rural Appraisal (PRA) and Asset-Based Community Development (ABCD), with the active involvement of MSME actors. The program stages involve field observations, preparation, implementation, and socialization activities. The results show that the existing potential of MSMEs falls into the